Readiness of Sub-Saharan Africa Healthcare Systems for the New Pandemic, Diabetes: A Systematic Review - Bernardo Nuche-Berenguer; Linda E. Kupfer (Journal of Diabetes Research)
Background. Effective health systems are needed to care for the coming surge of diabetics in sub-Saharan Africa (SSA). Objective. We conducted a systematic review of literature to determine the capacity of SSA health systems to manage diabetes. Methodology. We used three different databases (Embase, Scopus, and PubMed) to search for studies, published from 2004 to 2017, on diabetes care in SSA. Results. Fifty-five articles met the inclusion criteria, covering the different aspects related to diabetes care such as availability of drugs and diagnostic tools, the capacity of healthcare workers, and the integration of diabetes care into HIV and TB platforms. Conclusion. Although chronic care health systems in SSA have developed significantly in the last decade, the capacity for managing diabetes remains in its infancy. We identified pilot projects to enhance these capacities. The scale-up of these pilot interventions and the integration of diabetes care into existing robust chronic disease platforms may be a feasible approach to begin to tackle the upcoming pandemic in diabetes. Nonetheless, much more work needs to be done to address the health system-wide deficiencies in diabetes care. More research is also needed to determine how to integrate diabetes care into the healthcare system in SSA.